Assessment of treatment response in hepatocellular carcinoma: a review of the literature. (June 2013) - Maida, Marcello; Cabibbo, Giuseppe; Brancatelli, Giuseppe; Genco, Chiara; Alessi, Nicola; Genova, Claudio; Romano, Piero; Raineri, Maurizio; Giarratano, Antonello; Midiri, Massimo; Cammà, Calogero
Hepatocellular carcinoma (HCC) has a high incidence all over the world. Even if the primary end point of treatment of HCC is survival, radiological response could be a surrogate end point of survival, and could have a key role in clinical management. Since 1950 several radiological response criteria have been applied; however, it was not until 2000 that specific criteria for HCC were introduced by the European Association for the Study of the Liver (EASL), and these were then standardized in 2010 with the development of the modified Response Evaluation Criteria for Solid Tumors (mRECIST) for HCC. The purpose of this brief review is to compare data in literature regarding the application and the performance of mRECIST in clinical practice, and to discuss unclear and open issues.